Magnetic induced wet-spinning of graphene oxide sheets grafted with ferroferric oxide and the ultra-strain and elasticity of sensing fiber. (1st August 2019) - Zhang, Huanxia; Wu, Wen; Cao, Jianda; Tong, Mingqiong; Xu, Hong; Mao, Zhiping; Ma, Hui
Abstract: One dimensional neat reduced graphene oxide (RGO) fiber has low elongation and elasticity under external force, hindering its promising applications in electronics, sensors, etc. In our work, the RGO fibers with wrinkled packing structure of sheets were fabricated by magnetic induced wet-spinning of graphene oxide (GO) sheets grafted with ferroferric oxide (GFO) dope and followed by chemical reduction. The value of ultimate strain for RMGFO12.5 fiber was up to 51.97%, which was 9 times of RGO fiber (5.6%). The value of creep recovery of neat RGO fiber was 28.2%, and this value could reach up to 75.0% for RMGFO12.5 fiber with magnetic field induction, maintaining the ultra-strain and elastic property. Such RGO fibers with wrinkled packing structure will yield great advances in ductibility, elasticity and electromechanical properties and have potential high-tech applications, including wearable electronics, strain sensors, e-skins, etc. Graphical abstract: Image 1 Highlights: The MRGO and RMGFO fibers were obtained by magnetic induced wet-spinning assembly. The value of ultimate strain for RMGFO12.5 fiber was up to 51.97%. The RMGFO12.5 fiber exhibits high electromechanical properties.